2017
DOI: 10.1016/j.anireprosci.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of antral follicular blood flow velocity to superovulatory responses in ewes

Abstract: The aim of this study was to examine the association between antral follicular blood flow velocity and the response of ewes to hormonal ovarian superstimulation. Ten Santa Inês ewes were subjected to a short- (7days; Group 1) or long-term (13days; Group 2) progesterone (CIDR; InterAg, Hamilton, New Zealand) priming, and a superovulatory treatment with porcine follicle-stimulating hormone (pFSH; Folltropin-V; Bioniche Animal Health, Belleville, ON, Canada), given twice daily for four consecutive days in decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…Sanchez‐Dávila et al () reported similar number of CLs in response to 145 and 215 mg of total dose of pFSH for superovulation in goats whereas lower ovarian response was recorded when 80 mg was used; the same was recorded to produce transferable embryos. The number of CLs observed in this experiment was greater than observed by Oliveira et al () with the same protocol of superovulation in Santa Inês ewes using 200 mg of total dose of pFSH. Therefore, the reduction of total dose of pFSH in relation to the commonly used in small ruminants (200–256 mg; Oliveira, ) points to be beneficial; however, there seems to be a limit to this reduction.…”
Section: Discussioncontrasting
confidence: 66%
“…Sanchez‐Dávila et al () reported similar number of CLs in response to 145 and 215 mg of total dose of pFSH for superovulation in goats whereas lower ovarian response was recorded when 80 mg was used; the same was recorded to produce transferable embryos. The number of CLs observed in this experiment was greater than observed by Oliveira et al () with the same protocol of superovulation in Santa Inês ewes using 200 mg of total dose of pFSH. Therefore, the reduction of total dose of pFSH in relation to the commonly used in small ruminants (200–256 mg; Oliveira, ) points to be beneficial; however, there seems to be a limit to this reduction.…”
Section: Discussioncontrasting
confidence: 66%
“…The flow rate was temporally set at 450 μL/min for the time to quickly fill the circuit and then regulated to 50 or 100 μL/min, according to the experimental design. Flow rates were chosen based on previous studies in the sheep which reported that ovarian blood flow gradually decreases from the order of milliliters/min in the ovarian artery [ 51 , 52 ], to microliters/min in the capillary network around the developing follicles, varying in relation to various aspects such as the anatomical district and the ovarian cycle stage [ 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…During its development, although not exposed directly, but through the mediation of theca and granulosa cells, the COC receives nutrients and oxygen supply by continuous diffusion from the microcapillary network that surrounds the follicle. Ovarian blood flow rates range from milliliters/minute (at ovarian arterial level) to microliters/minute (at follicular capillary beds of antral follicles) [ 51 , 52 , 53 , 54 ]. In a previous study, we found that millifluidic IVM (mIVM) improved oocyte mitochondrial membrane potential, intracellular ROS levels, and mitochondria/ROS colocalization, markers of healthy oocyte cytoplasmic maturation.…”
Section: Introductionmentioning
confidence: 99%
“…The HVDA was regarded as an upper and lower quarter of the Doppler scale bar that corresponds to the velocity range of 0.04 to 0.08 m/s. All colour pixels were detected using the 'Count/size' tool and subsequently converted to SI units (Oliveira et al, 2017).…”
Section: Ultrasonographic Assessmentsmentioning
confidence: 99%